Improving the aesthetic culture of students during the interrelated studying Ukrainian and foreign literature (based on the special course "Topical issues of Ukrainian and foreign literature") (Pedagogy of Higher and Secondary Education, 2012)
Papushina V. Improving the aesthetic culture of students during the interrelated studying Ukrainian and foreign literature (based on the special course "Topical issues of Ukrainian and foreign literature").In the article there has been substantiated the meaning of special course «Topical issues of Ukrainian and Foreign Literature» for the forming of an aesthetic culture of students, there have been viewed forms and methods of increasing the aesthetic culture of students as based on the materials of the given special course, namely when studying I. Nechuy-Levitsky’s novel «Clouds» and I. Turhenyev’s collection of short stories «Hunter’s notes».
Keywords: aesthetic culture; comparative analysis; highly literary works; individual tasks; group work; discussion